2011
DOI: 10.1038/jid.2010.274
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Studies of Tyrosinase Variants Among Indian Oculocutaneous Albinism Type 1 Patients

Abstract: Collagenolytic activities with differentiation of the cultured cells from the murine hair apparatus. J Dermatol Sci 13:83-6 Paus R, Krejci-Papa N, Li L et al. (1994) Correlation of proteolytic activities of organ cultured intact mouse skin with defined hair cycle stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…The exact pathogenicity of the variant is yet to be determined, but there is some evidence that there is reduced enzymatic activity of tyrosine hydroxylase and DOPA oxidase when the Tyr192 variant allele was compared with the Ser192 wild-type allele. 23 In NYS-012, we identified a homozygous genomic variant (hg19 chr11:g. 88910354A>G) upstream from the transcription start site for the TYR gene (c.-768A>G; Supplementary Figure S3). This was a rare variant that has previously not been reported in the literature or in control databases (1000 genomes project, NHLBI ESP exomes or Exomes Aggregation Consortium (ExAC)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact pathogenicity of the variant is yet to be determined, but there is some evidence that there is reduced enzymatic activity of tyrosine hydroxylase and DOPA oxidase when the Tyr192 variant allele was compared with the Ser192 wild-type allele. 23 In NYS-012, we identified a homozygous genomic variant (hg19 chr11:g. 88910354A>G) upstream from the transcription start site for the TYR gene (c.-768A>G; Supplementary Figure S3). This was a rare variant that has previously not been reported in the literature or in control databases (1000 genomes project, NHLBI ESP exomes or Exomes Aggregation Consortium (ExAC)).…”
Section: Resultsmentioning
confidence: 99%
“…The Tyr192 variant allele was associated with reduced enzymatic activity of tyrosine hydroxylase and DOPA oxidase when compared with the Ser192 wild-type allele. 23 Further functional work is necessary to understand the exact effects of both these variants on transcription and translation of TYR .…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that defects in TYR cause albinism in 58% (36/62) of the cases [1] (and unpublished data; see Figure 1). Functional assays with missense mutations proved that none of mutants are enzymatically active and are retained in the endoplasmic reticulum [1].…”
Section: Resultsmentioning
confidence: 55%
“…Functional assays with missense mutations proved that none of mutants are enzymatically active and are retained in the endoplasmic reticulum [1]. Screening of the remaining cases (43%) revealed OCA2 to be the second common locus followed by SLC45A2 [2] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Functional studies have shown the R402Q polymorphism produces a thermolabile enzyme, retained by the cells endoplasmic reticulum, with a 75% reduction in catalytic activity compared to the wild-type 15, 22, 23 ; and S192Y results in a 40% reduction of tyrosinase enzymatic activity 24 . Multiple OCA1 studies have shown the R402Q allele is strongly associated with albinism patients with only one mutation 12, 17, 20 .…”
Section: Introductionmentioning
confidence: 99%